Determination of maturity stage, after ripening period, and seed storability of upland rice seeds at various phosphorus fertilizer doses - Irfan Firmansyah; Eny Widajati; Maryati Sari; Heni Purnamawati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
The increasing demand for rice makes upland rice a promising alternative. However, one major challenge in upland rice cultivation is the availability of high-quality seeds. This study aimed to determine the physiological seed maturity, after-ripening period, storage longevity, and optimal fertilizer dose to produce high-quality IPB 10G Tanimar. The research used a split-plot randomized complete block design with two factors and three replications. The main plot was phosphate fertilizer doses (50, 100, and 150 kg ha-1 SP-36), and the sub-plot was seed maturity stages (112, 116, 120, 124, and 128 days after planting(DAP). The results showed that fertilizer dose had no significant effect on vegetative and generative growth. The application of 100 kg ha⁻¹ P fertilizer produced the best seed quality based on the initial vigor index. The best maturity stage was 124 DAS with a heat unit of 2,505 °Cd, as indicated by the parameters of initial vigor index, germination rate during storage, and storability. The shortest after-ripening period was also found at 124 DAS, with the minimum germination rate (>80%) achieved one week after storage (WAS). The best storage vigor at the end of the observation period (8 WAS) was at 124 DAS, with a germination rate of 79.67% and a vigor index of 21.89%. Keywords: high-quality seed; heat unit; phosphate fertilizer; storage longevity; vigor index